Toward An Economic Theory of Multilateral Development Banking - Schwartz, Gerd. (Washington, D.C. : International Monetary Fund, 1993)
This paper addresses an apparent lack of economic theory in the analysis of multilateral development bank (MDB) behavior. A simple comparative statics model that is adapted from the credit union literature is used to predict potential areas of conflict, agreement, and indifference between MDB member countries, analyze lending policies against the background of distributional conflicts, and show how various institutional reforms may improve efficiency and overall member country benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet